Analysis of the Experience of Dyscalculia Children in Completing Addition Operations in Upper Elementary School Classes - Rizqi Siregar, Muhammad; Sriyanto, Sriyanto (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to identify the forms of addition difficulties experienced by students with dyscalculia and examine the strategies used to overcome these obstacles. Method: A phenomenological approach was applied through semi-structured interviews, naturalistic observations, and document analysis involving high-grade students, teachers, and parents selected purposively. Data analysis was conducted through data reduction, open coding, theme categorization, and member checking to ensure credibility. Results The results showed that addition difficulties arise in several aspects, including poor memory for arithmetic facts, misconceptions of place value, reliance on manipulatives, use of inefficient compensatory strategies, and high cognitive load on tiered problems. Emotional and social factors such as math anxiety and inconsistent family support also exacerbate children's obstacles. Novelty: These findings confirm that the experience of dyscalculia is multidimensional, so interventions need to include basic numerical reinforcement, cognitive load management, anxiety reduction, and ongoing collaboration between teachers and parents